2011
DOI: 10.1080/03602559.2011.557818
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid Materials Based on Modified Halloysite and Unsaturated Polyester Resin

Abstract: New hybrid materials based on unsaturated polyester resin and modified halloysite with different coupling agents were synthesized. The effect of functional groups grafted on the surface of halloysite against the properties of the final hybrids was studied using different characterization methods. The results of dynamic mechanical analyses showed that the glass transition temperature value of hybrids was strongly influenced by the halloysite modifier type. The concentration of halloysite and the modifier agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The modification of PCH with silane coupling agents (APTES and GPTMS) was highlighted by the apearance of new peaks at 2927 cm -1 (APTES) and 2951 cm -1 (GPTMS) attributed to the streaching vibrations of C-H from CH 2 groups of the coupling agents. Similar results were reported for various inorganic clays (halloysite, montmorillonite, kaolinite, MCM) modified with silane coupling agents [9,[14][15][16].…”
Section: Results and Discussion Characterization Of Functionalized Psupporting
confidence: 86%
“…The modification of PCH with silane coupling agents (APTES and GPTMS) was highlighted by the apearance of new peaks at 2927 cm -1 (APTES) and 2951 cm -1 (GPTMS) attributed to the streaching vibrations of C-H from CH 2 groups of the coupling agents. Similar results were reported for various inorganic clays (halloysite, montmorillonite, kaolinite, MCM) modified with silane coupling agents [9,[14][15][16].…”
Section: Results and Discussion Characterization Of Functionalized Psupporting
confidence: 86%
“…Typically, the outer diameter and inner diameter of HNTs are about 10-50 nm and 5-20 nm, respectively, while the length of HNTs is about 0.5-2 lm. HNTs are an environmentally-friendly natural inorganic nanometer material [2], which has been widely used in polymers as inorganic filler to promote the properties of polymeric materials [3][4][5][6][7][8][9][10][11][12][13]. Accordingly, the dispersion of particulate nano-fillers in polymer matrix and the filler-rubber interaction are two critical factors in determining the ultimate performance of polymer/HNTs nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite nanotubes (HNTs) are one of a few natural nanomaterials, which are a type of natural silicates with nanotubular particles. Chemically similar to kaolin, HNTs have a molecular formula of Al 2 Si 2 O 5 (OH) 4 ÁnH 2 O. The nanotubular structure is evolved by rolling up the layers of kaolinite under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite-epoxy nanocomposites with improved particle dispersion were reported by Deng et al [38] and Ye et al [39] The results demonstrated that blending epoxy with 2.3 wt% halloysite nanotubes increased the impact strength by four times without scarifying flexural modulus, strength, and thermal stability. Indeed, Garea et al [40] used HNTs to improve the properties of unsaturated polyester resin (UPR). They modified HNTs with two coupling agents, triethoxyvinylsilane and γ-aminopropyltriethoxysilane.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Garea et al. [ 40 ] used HNTs to improve the properties of unsaturated polyester resin (UPR). They modified HNTs with two coupling agents, triethoxyvinylsilane and γ‐aminopropyltriethoxysilane.…”
Section: Introductionmentioning
confidence: 99%